The Effect of the Principal's Situational Leadership Style and the Teacher's Work Commitment to the Implementation of Teaching Tasks for Public Elementary School Teachers - Fitra Dewi; Anisah; Syahril; Sulastri (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
This research is motivated by the results of the author's observations regarding the influence of the principal's situational leadership style and teacher's work commitment to the implementation of the teaching duties of public elementary school teachers in Nanggalo District which shows that the situational leadership style of the school principal and teacher work commitment is low and the implementation of teacher teaching tasks is still not good. The purpose of this study was to obtain data and information about (1) the positive influence of the situational leadership style of the school principal on the implementation of the teaching duties of public elementary school teachers in Nanggalo sub-district, (2) the positive effect of teacher work commitment on the implementation of teaching duties of public elementary school teachers in Nanggalo sub-district, This research is a correlational quantitative research with associative type. The population consisted of 261 PNS teachers and the sample was determined using the Cohran formula with an error rate of 5% using the Proportionate Stratified Random Sampling technique, 93 teachers were obtained. The research instrument uses a questionnaire with a Liker scale which has 5 alternative answers. Before the questionnaire was used, trials were carried out to determine its validity and reliability. Data analysis techniques were performed using multiple linear regression tests which were processed using SPSS version 23.0 The results of the data analysis show that there is a significant influence between the situational leadership style of the school principal on the implementation of teacher teaching tasks with tcount>ttable (749,666 > 27,380). There is a significant influence between the situational leadership style of the school principal and the teacher's work commitment to carrying out the teacher's teaching duties with a value of Fcount>Ftable (408.819> 3.09), so there is a significant influence between the situational leadership style of the school principal and the teacher's work commitment together to implementation of teacher teaching duties. The regression table shows a constant value of 27,380 and a regression coefficient of the X1 variable of 1. 251 and the value of the regression coefficient of variable X2 is 0.491. So the multiple linear regression equation used is 27,380+1,251X1+0,491X2+e. In the determination coefficient test, r² = 0.901 which indicates that the determination of the principal's situational leadership style variable and the teacher's work commitment to the implementation of the teacher's teaching duties is 0.90 or 90%.